Crystal structure of (E)-N-{2-[2-(2-chlorobenzylidene)hydrazin-1-yl]-2-oxoethyl}-4-methylbenzamide monohydrate - Purandara, H. (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, C(17)H(16)ClN(3)O(2)·H(2)O, an acylhydrazone derivative, contains a glycine moiety and two substituted benzene rings on either end of the chain. It crystallized as a monohydrate. The molecules adopt an E conformation with respect to the C=N double bond, as indicated by the N—N=C—C torsion angle of 179.38 (14)°. The molecule is twisted in such a way that the almost planar C(ar)—C(=O)—N(H)—C(H(2)) and C(H(2))—C(=O)N(H)—N=C—C(ar) [r.m.s deviations = 0.009 and 0.025 Å, respectively] segments are inclined to on another by 77.36 (8)°, while the benzene rings are normal to one another, making a dihedral angle of 89.69 (9)°. In the crystal, the water molecule links three molecules through two O—H⋯O and one N—H⋯O hydrogen bonds. The molecules are linked via pairs of N—H⋯O hydrogen bonds, forming inversion dimers with an R (2) (2)(14) ring motif. The dimers are linked by O—H⋯O hydrogen bonds, involving two molecules of water, forming chains along [100], enclosing R (2) (2)(14) and R (2) (2)(18) ring motifs. The chains are linked through C—H⋯O interactions, forming sheets parallel to (010). Within the sheets, there are C—H⋯π and parallel slipped π–π stacking interactions present [inter-centroid distance = 3.6458 (12) Å].